Delayed MTS(2s) e procedimentos de Training-IRAP: explorando eficácia, eficiência e seu formato de treino no estudo de relações derivadas - Silvestre, Marcello Henrique (2024)
A common method for the study of derived relations is the Matching-to-Sample (MTS) preparation. However, certain aspects of the procedure arguably hinder the emergence of new relations, such as different sources of stimulus control. Consequently, the investigation of other procedures seems justified. The Training-IRAP may be a plausible alternative. The primary objective was to compare the effectiveness of Delayed MTS(2s) and Training-IRAP procedures in terms of participant derived relations yield. The secondary objective was to compare the average number of training blocks needed per procedure. Due to additional components in the Standard Training-IRAP not found in MTS, some edits were made to the former procedure yielding two new versions: the Modified Training-IRAP and Delayed Modified Training-IRAP(2s). Sixty-eight students participated, 17 per group. Nine participants met yield criteria in the Delayed MTS(2s) group, three in the Standard TrainingIRAP group, 11 in the Modified Training-IRAP group, and 12 in the Delayed Modified Training-IRAP(2s) group. The average number of blocks to complete training phases was lowest for the Delayed MTS(2s) and Delayed Modified Training-IRAP(2s) groups. The formats of the procedures and implications of the findings toward an overarching goal of greater precision, scope and depth in conceptual, experimental and applied settings are discussed